IDENTIFIKASI 26 ISOLAT BAKTERI ENDOFITIK DAN FILOSFER PADI DENGAN ANALISIS SEKUEN16S RDNA - Nurul Hidayatun; Dwi N Susilowati; K Mulya K Mulya (Research Center for Biology-Indonesian Institute of Sciences, 2011)
The research was subjected to identify 26 endophytic and phyllosphere bacteria isolated from 4 rice varieties using sequencing method of 16S rDNA.The sequences were then aligned with reference sequence from Gen-Bank data library by BLAST program from NCBI to find the most related identity of the isolates analysed.The sequencing analysis revealed that some isolates have a high identity to Staphylococcus and Serratia (5 isolates each), Bacillus (4 isolates), Microbacteria (3 isolates), Pseudomonas (2isolates) and Klebsiella, Acidovorak, Bulkholderiaceae, Agrobacterium and Shewanella (1 isolate each). No specific isolate dominated in both endophytic and phyllosphere group, nor host-specific isolate found in the four rice varieties.